2016
DOI: 10.1021/acschembio.6b00980
|View full text |Cite
|
Sign up to set email alerts
|

Trapping Reactions of the Sulfenyl and Sulfinyl Tautomers of Sulfenic Acids

Abstract: Sulfenic acids react as both nucleophiles and electrophiles, which may be attributable to interconversion between sulfenyl and sulfinyl tautomers. We demonstrate one-pot trapping of both tautomeric forms of glutathione sulfenic acid by LCMS. The sulfinyl tautomers are characterized by reaction with nucleophilic reagents such as dimedone and cyanide, giving unique products that are analogous to corresponding adducts of aldehydes. Likewise, we show that aldehyde reactive reagents such as silyl enol ethers also r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In a recent report, we demonstrated that the sulfenyl and sulfinyl tautomeric forms, Scheme 3, of glutathione sulfenic acids can be trapped by various C-type nucleophilic traps like dimedone, 1-trimethylsiloxycyclohexene, and cyanide [39]. The dual reactivity of sulfenic acid as nucleophile and electrophile towards trapping agents produced unique products that are well characterized by LC/HDMS studies.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent report, we demonstrated that the sulfenyl and sulfinyl tautomeric forms, Scheme 3, of glutathione sulfenic acids can be trapped by various C-type nucleophilic traps like dimedone, 1-trimethylsiloxycyclohexene, and cyanide [39]. The dual reactivity of sulfenic acid as nucleophile and electrophile towards trapping agents produced unique products that are well characterized by LC/HDMS studies.…”
Section: Resultsmentioning
confidence: 99%
“…1 . The electrophilic and nucleophilic characteristics of HSOH is also evident in its reaction with 1-trimethylsiloxycyclohexene ( S4 ), which yields unique products analogous to those seen in glutathione peroxidations [33] .
Fig.
…”
Section: Sulfenic Acid Hsohmentioning
confidence: 99%
“…These SOS are highly reactive and notoriously difficult to characterize in biologically relevant conditions, and unlike their alkyl homologs, there is a little data on SOS generation and speciation during H 2 S oxidation [29] , [30] , [31] , [32] . We recently reported trapping of both sulfenyl and sulfinyl tautomers of oxidized glutathione derivatives using a combination of selective nucleophilic and electrophilic trapping reagents and characterization by high resolution LC MS [33] . We hypothesize that the physiological effect of H 2 S may derive from SOS, and thus we investigated their formation in biologically relevant conditions using similar methods, in situ derivatization with nucleophilic sulfenyl trapping reagent dimedone [34] , [35] and electrophilic reagents iodoacetamide, as well as mono- and di-bromobimane [36] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is quite reactive, and can undergo a multitude of reactions resulting in a wide variety of chemical species. For example, sulfenic acid can undergo further oxidations to more stable metabolites (such as sulfinic and sulfonic acids), react with another sulfenic acid (disproportionation reaction) to form a free thiol and a sulfinic acid, react with nucleophiles (like thiols) resulting in mixed disulfides [ 13 ], react with cyanide (resulting in thiocyanate), react with thiocyanate (resulting in dithiocyanate) [ 14 ], or even react with nucleophilic moieties of proteins, commonly with cysteine residues, to form covalent adducts [ 11 ]. Due to this highly reactive behavior of sulfenic acid intermediates, detection is especially challenging.…”
Section: Introductionmentioning
confidence: 99%